PENGARUH PENDIDIKAN KESEHATAN GIGI DENGAN LITERASI DIGITAL TERHADAP PENGETAHUAN DAN PERILAKU PERAWATAN GIGI PADA ANAK USIA SEKOLAH DASAR SE-TANGERANG - Anggrayni, Nuke; Susilowati, Yuni (Nusantara Hasana Berdikari, 2021)
The problem of cavities is still a lot of complaints by both children and adults and cannot be allowed to be severe because it will affect the quality of life where they will experience pain, discomfort, disability, acute and chronic infections, eating and sleeping disorders and have a high risk of being treated. in the hospital, which causes high medical costs, disruption of daily activities and reduced learning time at school. . The method used in this study is a pre-experimental method with a one-group pretest-posttest design. The research instrument used was a questionnaire in the form of a google form link, the sample in this study used an accidental sampling technique totaling 100 respondents with an age range of 6-12 years, and data analysis using the Wilcoxon test. The results of the study were based on the Wilcoxon test results obtained p-Value 0.000 <0.05, it can be concluded that Ha is accepted, which means that there is an effect of dental health education on knowledge and dental care behavior.